Analisis Nilai-Nilai Musyawarah Pada Film Anak Indonesia “5 Elang” - Sekar Arum Pramudita; Muhamad Taufik Hidayat (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aimed to analyze and describe the contents of the moral values of deliberation in a movie entitled